2010
DOI: 10.2478/v10014-010-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

Relation of total antiradical activity and total polyphenol content of sweet cherries (Prunus avium L.) and tart cherries (Prunus cerasus L.)

Abstract: In present study the quantification of total phenolics content (TPC), total antioxidant activity (TAA) and their relation in sweet and tart cherries were studied. Aqueous and pure polar solvents were used to compare the yield of present phenolic compounds in prepared extracts. The solubility of phenolics was the most effective in sweet cherry extracts with using of 50 % methanol and in tart cherry extracts with using of 50 % acetone. The yield of TPC of both tested cherry fruit extracts was higher with pure me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
0
21
2
Order By: Relevance
“…Other previous reports on the total polyphenol content of sour cherries varied from 78 to 500 mg/100 g (Kim et al 2005, Bonerz et al 2007, Dragović-Uzelac et al 2009). Higher concentrations of polyphenols in our investigation as compared to other studies may be the result of differences in extraction and measuring protocols (Melicháčová et al 2010) performed by a group of several authors in polyphenol determination but also it can be a consequence of cultivar impact, climatic conditions and agricultural measures in specific location were sampling is done.…”
Section: Resultscontrasting
confidence: 44%
See 1 more Smart Citation
“…Other previous reports on the total polyphenol content of sour cherries varied from 78 to 500 mg/100 g (Kim et al 2005, Bonerz et al 2007, Dragović-Uzelac et al 2009). Higher concentrations of polyphenols in our investigation as compared to other studies may be the result of differences in extraction and measuring protocols (Melicháčová et al 2010) performed by a group of several authors in polyphenol determination but also it can be a consequence of cultivar impact, climatic conditions and agricultural measures in specific location were sampling is done.…”
Section: Resultscontrasting
confidence: 44%
“…9: 389-395 Plant Soil Environ. doi: 10.17221/472/2017 to the different extraction and measuring protocols (Melicháčová et al 2010) but also the strong impact of cultivar and environmental factors during the growing season cannot be discarded. Khoo et al (2011) found variation in the anthocyanin content among 34 sour cherry cultivars in a range from 21 to 272 mg malvidin-3-glucoside equivalents/100 g of fresh fruit weight.…”
Section: Resultsmentioning
confidence: 99%
“…Sour cherries are comparatively rich in anthocyanins and possess high antioxidant activity (Siddiq et al 2011), yet surprisingly few studies have compared antioxidant capacities of several sour cherry cultivars (Simunic et al 2005;Veres et al 2006). Values of total antioxidant activity of tart cherry extracts in Melichacova et al (2010) ranged from 5.4%-9.9% of inhibition of DPPH, and some of the Iranian sour cherry genotypes examined here had significantly higher values.…”
Section: Total Antioxidant Activitymentioning
confidence: 65%
“…The DPPH radical scavenging assay is commonly employed to evaluate the ability of antioxidant to scavenge free radicals (Melichacova et al 2010),…”
Section: Total Antioxidant Activitymentioning
confidence: 99%
“…In this study significant increases were also found in the content of total phenolic compounds and antioxidant power during the ripening of fruits. Additionally, different solvents were applied for comparing the antioxidant capacity and the yield of total phenolic compounds present in the extracts of sour and sweet cherries [40]. It was found that the solubility of phenolic compounds was more effective in extracts of sweet cherries with use of methanol at 50% and in extracts of sour cherries with the use of acetone at 50%.…”
Section: Sources and Their Antioxidant Powermentioning
confidence: 99%